Perbedaan Rata-Rata Harga Saham Sektor Perbankan dan Farmasi dengan Perhitungan Interval Kepercayaan - Mayanti, Yuni; Ruhliandini, Putri Zafira (INDUSTRIAL ENGINEERING JOURNAL of the UNIVERSITY of SARJANAWIYATA TAMANSISWA, 2024)
The capital market serves as a key economic indicator, reflecting the performance of various industrial sectors, including the banking and pharmaceutical sectors. The Covid-19 pandemic in 2020 had distinct impacts on these two sectors, which were reflected in the movement of their stock prices. This study aims to analyze the differences in the average stock prices of the banking and pharmaceutical sectors listed on the Indonesia Stock Exchange (IDX) in 2020 using the 99% confidence interval method. The data used in this study consists of stock prices obtained from the official IDX website, with a sample of 10 banking companies and 10 pharmaceutical companies selected through the purposive sampling method. The analysis results indicate a difference in average stock prices of 932.5 ± 11,388 with a 99% confidence level. The calculation using the t-student table with t = 2.88 confirms that there is a difference in the average stock prices of the banking and pharmaceutical sectors in 2020. Although, on average, the banking sector has higher stock prices, the confidence interval shows a relatively wide range, suggesting the possibility of no statistically significant difference. These findings provide valuable insights for investors in making informed investment decisions and for capital market regulators in maintaining market stability.